Analysis of Bank's Financial Performance Using The RGEC at PT. Bank Central Asia Tbk from 2017 to 2021 - Rabiulan Indah Tadarus; Achmad Nur Sholeh (Indonesian Financial Review, 2022)
This study aims to analyze the financial performance of PT. Bank Central Asia Tbk covering aspects of Risk Profile, Good Corporate Governance (GCG), earnings and Capital as a whole. The type of research used by the author is descriptive research. The population and sample in this study are financial statements for the period 2017-2021 at PT. Bank Central Asia Tbk. The variables in this study are financial performance and RGEC ratio. The type of data used in this research is quantitative data. The source of data used by researchers is secondary data. The data collection technique used in this research is documentation in the form of financial reports. The results of the financial performance assessment with the RGEC ratio indicate that the health level of PT. Bank Central Asia Tbk in 2017-2021 based on the RGEC method is very healthy.